Ab initio study of fundamental properties of XAlO3 (X = Cs, Rb and K) compounds - Berri, Saadi (H. : ĐHQGHN, 2018)
The structural, electronic, magnetic and optical properties of suggestedXAlO3(X¼Cs, Rb and K) pe-rovskites under pressure effects are investigated by means of thefirst-principles calculations with the technique of the Full Potential Linearly Augmented Plane Wave (FP-LAPW) implemented within Wien2k computer package. The electronic exchange correlation energy is determined by using Generalized Gradient Approximation together with SpineOrbit Interaction (GGAþSOI). The lattice constant, bulk modulus and its pressure derivative are calculated. Half-metallicity was preserved at ranges of 4.03-4.19 Å, 4.03-4.18 Å and 3.74-4.09 Å for the CsAlO3, RbAlO3 and KAlO3 compounds, respectively. The largest spin-flip gaps are found in the spin up channel, corresponding to a magnetic moment of 2 mB/f.u. Optical properties are also studied. Dielectric function, refractive index, and loss energy are calculated and discussed. The present work presents the first theoretical study of the perovskites of interest and still awaits experimental confirmations.